Redescription of Isotominella geophila Delamare Deboutteville, 1948 from Algeria (Collembola, Entomobryomorpha, Isotomidae), a second world record for an Ivory Coast species - Jordana, Rafael; Hamra-Kroua, Salah; Baquero, Enrique (Zootaxa, 2009)
Isotominella geophila Delamare Deboutteville, 1948, from Massif Edough in Northeast Algeria, has been found for the second time and is redescribed. It is separated from all other genera of Isotomidae by the following combination of characters: absence of eyes and pigment, PAO oval, not subdivided, shorter than width of antennal base, dens partially crenulated, dental chaetotaxy with more than six setae (13+4), posterior central S-setae on thoracic tergite II to abdominal tergite IV in p-row, S-seta on abdominal tergite V not thickened and mucro bidentate. This species exhibits sexual dimorphism.